How high should boys sing? [ gender, authenticity and credibility in the young male voice - Ashley, Martin , 1953- (Farnham, England Burlington, VT : Ashgat, 2009)
Martin Ashley presents a unique consideration of boys' singing that shows the high voice to be historically, culturally and physiologically more problematic even than is commonly assumed. Through Ashley's extensive conversations with young performers and analysis of their reception by 'peer audiences', the research reveals that the common supposition that 'boys don't want to sound like girls' is far from adequate in explaining the 'missing males' syndrome that can perplex choir directors. The book intertwines the study of singing with the study of identity. --from publisher description
1. The background -- 2. Singing as social control of boyhood -- 3. Physiology of the young male voice -- 4. Subjectivity and agency in the young male voice -- 5. Admiration of the boy -- 6. A child doing a man's work in a man's world -- 7. Angels in the market place -- 8. We can't sing like men, so we won't sing at all -- 9. Ambassadors and mediators -- 10. The future
Description based on print version record
Includes bibliographical references and index
Keywords: Boys -- Psychology; Singing -- Instruction and study -- Great Britain; Singing -- Psychological aspects; Singing -- Social aspects; Voice, Change of